Seks Onlen, Media Sosial, dan Gender - Hildawati Hildawati (Emik, 2018)
Normatively sexual relations are carried out directly by a pair of different sexes. However, now sex can be done in various ways, including by using communication technology to be able to have sex without physical contact and long distance, which is known as online sex. The research setting is focused on social media in the form of online sex service provider accounts. Fifteen participants get involved in this study, who offered their online sex service. I combined in-depth interview and observation as my data collection techniques. The study shows that online sex is different based on the type of technology used and can be categorized into three types, namely VCS (video call sex), PS (phone sex), and CS (chat sex). While VSC online sex is carried out through feature video call, PS online sex is carried out through voice telephone conversations, and CS online sex is done through chatting on social media Instagram or Whatsapp. Online sex providers use Instagram accounts not only as a medium to promote online sex services, but also as a media to find prospective online sex customers. The objective orientation between female online sex providers and male online sex service providers shows differences based on gender. Making money is the primary objective of of female sex online providers, while for male service providers, seeking sexual satisfaction is their primary objective with a slogan "we are equally satisfied". But, some customers can have their services for free as long as they both agree, others ask to have video or nude photo from their customers. Online sex is carried out not only in the form of sighing, speaking vulgarly, looking naked (either half naked or full body), to masturbating. This can also be continued with non-online sex through booking out (BO), depending on the agreement between sex online provider and the customer or between sex online service providers. It is argued in this article that social media has become a medium not only to run one’s business, but also to have online sex.